EXPERIENTAL AND LOGICAL FUNCTION IN NOMINAL GROUP STRUCTURE OF MALE AND FEMALE UNDERGRADUATE STUDENTS’ THESIS TITLES - Siska . Pratiwi; Amrin . Saragih; Rahmad . Husein (LINGUISTIK TERAPAN, 2022)
The objective of this study was to find out the elements of experiential and logical function in nominal group structure of male and female undergraduate student’s thesis title of male and female students. This study applied qualitative research design. The data of the study was the nominal groups on undergraduate thesis title of State University of Medan students who have finished the last assignment in 2017, 2018, 2019, 2020 and 2021, majoring in English Education. The source of the data was taken from official site Digital Repository State University of Medan (digilib.unimed.ac.id). The results revealed that based on experiential function, there were Deictic, Classifier, Thing and Qualifier with no Numerative and Epithet, Thing/Head absolutely found in every title; and based on logical function, Premodifier, Head and Postmodifier found in all titles. This result showed that there was difference in male and female titles that female dominated the quantity and used more various elements in both functions.